Meningkatkan Perkembangan Sosial Melalui Bermain Balok Pada Anak Usia 5-6 Tahun di TK Kemala Bhayangkari 14 Mandailing Natal - Devi Arisandi; Solikah Solikah; Fitria Mareta Sari (Jurnal Pendidikan Tuntas, 2023)
Social emotional development is important to develop because it requires the ability to manage emotions and interact socially with others but in Kemala Bhayangkari 14 Kindergarten it has not developed properly so it needs to be given action in a study. The type of research is Classroom Action Research. The goal is to improve social development through playing blocks in children aged 5-6 years at Kemala Bhayangkari 14 Mandailing Natal Kindergarten. The results of cycle 1 research, namely children in the Not Developing category remaining 45%, then for the Starting to Develop category amounted to 30%. An increase also occurred in the Developing As Expected category which became 15%, and Developing Very Well obtained 10%. Furthermore, based on the results of the reflection in Cycle I, the researcher compiled a plan for implementing the action in Cycle II. With the acquisition of values as follows: Children who are in the Not Developing category become 0%, while children in the Starting to Develop category remain 5%. Furthermore, children who are in the Developing As Expected category become 75%, the rest are in the Very Good Developing category with the acquisition of 20%. Thus, increasing the average social-emotional in children aged 5-6 years at Kemala Bhayangkari 14 Mandailing Natal Kindergarten has met the success indicators so that it does not require reflection action and the research is considered complete. Keywords: Social, Emotional, Playing Blocks